Mengulik Metode Tafsir Ayat-Ayat Ekonomi (Tafsir Bi Al Matsur, Tafsir Bi Al Ra`Yi, Tafsir Bi Al Isyari) - Bella Mutiara Kasih; Taufik Warman Mahfuzh; Syamhudian Noor (AL-IBNOR, 2025)
This article discusses the interpretation approach, namely tafsir bi al matsur, tafsir bi al ra'yi, tafsir bi isyari. With the aim of knowing the explanation and differences of various approaches to the science of interpretation, namely tafsir bi al matsur, tafsir bi al ra'yi, tafsir bi isyari. This article uses qualitative research based on literature (library research) with a qualitative descriptive approach and descriptive analysis techniques. The results of this study show the differences in interpretation methods between tafsir bi al matsur, namely the method of interpreting verses using other verses or the hadith of the Prophet Muhammad, tafsir bi al ra'yi, namely interpretation taken based on ijtihad and the thoughts of the mufassir after knowing Arabic and its methods, legal arguments are addressed in the interpretation, while tafsir bi al isyari is an interpretation carried out based on existing or obscure signs and can be understood and known by people who have knowledge in their fields and have a high level of piety. Interpretation through interpretation of the verses of the Qur'an must be in accordance with or in line with the literal or apparent meaning of the verses of the Qur'an which are interpreted from various angles.